An Insight into Mechanical and Metallurgical Behavior of Hybrid Reinforced Aluminum Metal Matrix Composite. (10th October 2022) - Ashebir, Demeke Abay; Mengesha, Getinet Asrat; Sinha, Devendra Kumar
Abstract : Hybrid reinforced particulate aluminum matrix composite materials (HAMCs) are a breakthrough kind of material made by combining two or more distinct reinforcing components in the aluminum (Al) matrix. Composites with many reinforcing phases offer a superior overall mix of characteristics than composites with only one. This article's wide literature review of metal matrix composite (MMC) especially for aluminum matrix composites (AMC) was carried out. Discussions of various widely adopted synthesis methods such as stir casting and powder metallurgy have been presented. The effect of various reinforcement ceramic particles such as silicon carbide (SiC), aluminum oxide (Al2 O3 ), graphite (Gr) on the mechanical and metallurgical properties of MMC has been reviewed. The summary of various characterizations such as X-ray diffraction (X-RD), and optical microscopy (OM) including testing such as hardness, tensile, compressive, and tribological behavior has been discussed in detail to demonstrate a full grasp of the many features of HAMCs, such as manufacturing, physicomechanical properties, wear, and corrosion characteristics. Future developments and potentially useful materials as alternative reinforcements are discussed at the end of the review.